Novel alterations of CC2D1A as a candidate gene in a Turkish sample of patients with autism spectrum disorder. (17th October 2022) - Sener, Elif Funda; Onal, Muge Gulcihan; Dal, Fatma; Nalbantoglu, Ufuk; Ozkul, Yusuf; Canatan, Halit; Oztop, Didem Behice
Abstract: Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with large genetic background, but identification of pathogenic variants has proceeded slowly because hundreds of loci are involved in this complex disorder. CC2D1A gene firstly associated with the intellectual disability (ID) in a family with a large deletion. We aimed to contribute to the literature by sequencing this gene and by this way we report novel CC2D1A variations in patients with ASD. Methods: Forty families who have a child with a diagnosis of ASD were enrolled to the study. DNA samples were obtained from each family member. Bidirectional CC2D1A gene sequencing was performed with CEQ Cycle Sequencing Kit, and the products were analyzed on the Beckman CEQ 8000. All of the genetic analysis was conducted in Erciyes University Genome and Stem Cell Center (GENKOK). Results: According to the sequencing results, we defined new alterations in this gene with two SNPs in exon 15 and 19 (rs747172992 and rs1364074600) in our patients. We found a pathogenic variant in one patient. This variant was located in the acceptor region. Six of the variants were missense mutations. Additionally, six different benign variants were detected in 30 patients; however, they were not associated with ASD. Two patients carried multiple rare variants. Conclusion: In vitro and in vivo functional analysis with this gene will help to understand its contribution to ASD pathogenesis. Future studies may help to elucidate the underlying biological mechanisms of these variants leading to the autism phenotype.